Improvement of Mathematics Learning Process and Outcomes Using the Take and Give Model Assisted by Number Glass Media in Grade III Students at SDN 012/II Empelu - Dea Wahyu Ningsih; Puput Wahyu Hidayat; Reni Guswita (Green Publisher, 2026)
This study was conducted because the mathematics learning outcomes of third-grade students at SDN 012/II Empelu were still low, with only 29.4% of students achieving a passing grade. One of the causes is the lack of student activity in learning, such as rarely asking questions or expressing opinions. The purpose of this study was to improve the learning process and outcomes of students through the application of the Take And Give learning model. The method used was Classroom Action Research conducted in two cycles, each through the stages of planning, implementation, observation, and reflection. The research subjects were third-grade students at SD Negeri 012/II Empelu. The results showed a significant improvement, where in cycle I, the students' learning process reached a good category with an average of 52.94%, but did not meet the success criteria. The percentage of student learning mastery in cycle I was 58.82%, which, although it met the mastery criteria in terms of numbers, was not satisfactory. In cycle II, there was a significant improvement, both in terms of the learning process with an average of 82.35% and learning outcomes with a mastery rate of 82.35%, thus meeting the research success criteria. In conclusion, the application of the Take And Give learning model is effective in improving the learning process and outcomes of third-grade students at SDN 012/II Empelu.